IDENTIFYING FACTORS OF TREE RISK MANAGEMENT FOR LOCAL AUTHORITIES IN SELANGOR - Azlina Mat Salim; Nor Azilah Husin (International Journal of Accounting, Finance and Business, 2021)
The increasing tree risks in Selangor are a sign of unattended issues, lack ofmaintenance, and absence of standards. The local authorities may keep planting more treesbecause the intention was to make their city greener or attractive. However, as the BrundtlandCommission conceptualized in 1987, "sustainable development" as; paths of human progresswhich meet the needs and aspirations of the present generation without compromising theability of future generations to meet their needs; the need to make the environment safe is likelythe balance to the core aspiration. This study aims to identify factors of tree risk management.The research explored the relationship between the local governing factors and tree riskmanagement, considered their understanding of the role of tree risk management ingovernance. These differences shed those six aspects have criteria that are able to affecttree risk management and thus become important factors in managing tree risk in localauthorities of Selangor. The research finding suggested the measures and indicators indetermining the level of efficiency in the tree risk management of a local leader in Selangor.This study is hoped to offer knowledge contribution to the body of literature in determining theTree Risk Management to be used by all the local authorities in Selangor